Experiences of Inuit in Canada who travel from remote settings for cancer care and impacts on decision making - Janet Jull; Amanda J. Sheppard; Alex Hizaka; Inuit Medical Interpreter Team; Gwen Barton; Paula Doering; Danielle Dorschner; Nancy Edgecombe; Megan Ellis; Ian D. Graham; Mara Habash; Gabrielle Jodouin; et al. (BMC, 2021)
Abstract Background Inuit experience the highest cancer mortality rates from lung cancer in the world with increasing rates of other cancers in addition to other significant health burdens. Inuit who live in remote areas must often travel thousands of kilometers to large urban centres in southern Canada and negotiate complex and sometimes unwelcoming health care systems. There is an urgent need to improve Inuit access to and use of health care. Our study objective was to understand the experiences of Inuit in Canada who travel from a remote to an urban setting for cancer care, and the impacts on their opportunities to participate in decisions during their journey to receive cancer care. Methods We are an interdisciplinary team of Steering Committee and researcher partners ("the team") from Inuit-led and/or -specific organizations that span Nunavut and the Ontario cancer health systems. Guided by Inuit societal values, we used an integrated knowledge translation (KT) approach with qualitative methods. We conducted semi-structured interviews with Inuit participants and used process mapping and thematic analysis. Results We mapped the journey to receive cancer care and related the findings of client (n = 8) and medical escort (n = 6) ("participant") interviews in four themes: 1) It is hard to take part in decisions about getting health care; 2) No one explains the decisions you will need to make; 3) There is a duty to make decisions that support family and community; 4) The lack of knowledge impacts opportunities to engage in decision making. Participants described themselves as directed, with little or no support, and seeking opportunities to collaborate with others on the journey to receive cancer care. Conclusions We describe the journey to receive cancer care as a "decision chain" which can be described as a series of events that lead to receiving cancer care. We identify points in the decision chain that could better prepare Inuit to participate in decisions related to their cancer care. We propose that there are opportunities to build further health care system capacity to support Inuit and enable their participation in decisions related to their cancer care while upholding and incorporating Inuit knowledge.